Immersive Contexts and Oral Fluency Development Among ESL Learners in the United States: An Action Research Study - Muhammad Alrayes (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
This action research study employed a triangulated methodology, incorporating pre- and postquestionnaires, to explore the oral fluency development of six advanced ESL students. The study compared the impact of immersion in a U.S. target language environment with learning in a home culture context. Findings indicated that students who maximized their engagement with native English speakers within the target culture demonstrated significantly greater advancements in oral fluency compared to their peers who opted not to fully utilize the linguistic and cultural environment. This study emphasizes the transformative potential of immersive language learning experiences and contributes to the understanding of best practices in second language acquisition (SLA).